Islamic Educational Leadership in Ranah 3 Warna: An Integrative Model from a Modern Management Perspective - Jati, Rasi A’yun Andhini; Isnaini, Rohmatun Lukluk; Mulya, Sonia Sri Kencana (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2026)
This study examines the representation of Islamic educational leadership in Ahmad Fuadi’s novel Ranah 3 Warna and explores its relevance to contemporary educational management. Employing a descriptive qualitative approach, the study uses content analysis to examine the novel’s dialogues, narratives, and key events. The findings reveal that Islamic educational leadership is represented through five interrelated dimensions: (1) transformational leadership grounded in moral exemplarity, (2) visionary leadership fostered through a strong literacy culture, (3) empathetic relational leadership in conflict resolution, (4) adaptive leadership in responding to social change, and (5) moral-spiritual leadership rooted in family values. These findings suggest that Islamic leadership values extend beyond normative religious principles and offer strategic contributions to character development, literacy enhancement, conflict management, and institutional adaptability. Consequently, the model of Islamic educational leadership portrayed in the novel provides a contextually relevant framework for the management of contemporary Islamic educational institutions. The study concludes by recommending further empirical research to examine the applicability and effectiveness of this leadership model across diverse Islamic educational contexts. Abstrak: Penelitian ini menganalisis representasi kepemimpinan pendidikan Islam dalam novel Ranah 3 Warna karya Ahmad Fuadi serta relevansinya terhadap manajemen pendidikan modern. Penelitian ini menggunakan metode kualitatif deskriptif dengan analisis isi terhadap dialog, narasi, dan peristiwa dalam novel. Hasil penelitian menunjukkan bahwa kepemimpinan pendidikan Islam direpresentasikan dalam lima dimensi, yaitu kepemimpinan transformasional berbasis keteladanan moral, visioner berbasis literasi, relasional yang empatik dalam penyelesaian konflik, adaptif terhadap perubahan sosial, serta moral-spiritual yang berakar pada nilai keluarga. Temuan ini menegaskan bahwa nilai kepemimpinan Islam tidak hanya bersifat normatif-religius, tetapi juga relevan secara strategis dalam penguatan karakter, literasi, manajemen konflik, dan adaptasi lembaga pendidikan. Dengan demikian, model kepemimpinan Islam dalam novel ini memiliki relevansi kontekstual terhadap pengelolaan pendidikan Islam modern. Penelitian ini merekomendasikan kajian lanjutan empiris untuk menguji implementasinya pada berbagai lembaga pendidikan Islam.